Medieval clothing and textiles. - Netherton, Robin; Owen-Crocker, Gale R. (The Boydell Press, 2018)
The essays here continue in the Journal's tradition of drawing on a range of disciplines. Topics include evidence for dress in multicultural sixth-century Ravenna; the incidence of Byzantine and Oriental silks in ninth- to thirteenth-century Denmark; a new analysis of the chronology of and contexts for the French hood; an examination of the mysterious garment called a bliaut in French literature; a discussion of the vocabulary and loan words in Italian/Anglo-Norman mercantile transactions; and revelations that fashions in body hair were an important feature of women's appearance. -- Publisher description.